A four-year, mixed-family and community-based growth monitoring and promotion program using multi-level modeling to address undernutrition in children in Cambodia - Liu, Po-Yen; Lin, Yen-Ting; Chiou, Yee-Hsuan; Lee, Maw-Sheng (Frontiers in Public Health, 2025)
IntroductionChild undernutrition persists as a formidable public health issue in developing countries. Children afflicted by undernutrition are susceptibility to both physical and neurological repercussions. For several decades, initiatives focused on growth monitoring and promotion have been instituted to mitigate this pressing issue. Nevertheless, the prevalence rates of undernutrition across developing nations continue to provoke concern.MethodsBetween the years 2016 and 2019, we executed a family- and community-oriented growth monitoring and promotion initiative within a rural Cambodian village, specifically aimed at children under the age of five. This initiative employed a hybrid workforce comprising both full-time health professionals and community volunteers. Leveraging this robust capacity, we delivered small-group nutrition education sessions, family-centered nutrition counseling, and regular anthropometric assessments. In contrast to a cross-sectional methodology, we used multi-level modeling to explore the growth trajectories of children utilizing longitudinal z scores for height-for-age and weight-for-age. A systematic taxonomy of models was developed in a sequential framework to ascertain the most appropriate final model.ResultsOut of 533 enrolled children, 358 completed the growth monitoring program (GMP). At baseline, children older than 12 months had significantly lower height-for-age (HAZ) and weight-for-age (WAZ) scores, as well as higher rates of stunting and wasting, compared to younger children. These differences were no longer significant by the end of the program. Nonparametric trajectory analyses showed age-related differences in HAZ patterns, with initial declines followed by recovery in younger age groups, while WAZ trajectories remained relatively flat across all ages. Multilevel modeling indicated that both age at enrollment and time significantly influenced HAZ changes, while only age at enrollment affected WAZ. Older children exhibited steeper improvements over time, leading to convergence in growth outcomes with younger children.ConclusionAn extended and efficacious growth monitoring and promotion program has the potential to ameliorate the issue of undernutrition in developing countries.